Algaria overbergensis Hedd. & R.H.Zander, a new moss species from the Overberg Rûens Shale Renosterveld system of the Southwest Cape, South Africa. (3rd July 2022) - Hedderson, Terry A.; Zander, Richard H.
ABSTRACT: Introduction: The moss genus Algaria currently comprises a single species known only from the type locality. During recent bryological surveys of remnant Overberg Renosterveld patches, plants were collected that clearly belong to this genus but differ from the only known species in several critical respects. Here, we describe these as a new species. Methods: Specimens were rehydrated in the laboratory, dissected, and mounted in Hoyer's solution or polyvinyl alcohol–glycerine. Observations and measurements were made using standard stereo and compound microscopy. Spore anatomy was further investigated using scanning electron microscopy. Key results and conclusions: Algaria overbergensis Hedd. & R.H.Zander is described as a new species currently known from only three localities in Overberg Rûens Renosterveld. It is readily distinguished from its only congener ( Algaria natalieae Hedd. & R.H.Zander) by its rounder capsule with a domed to conical operculum, epapillose calyptra, much larger spores, and truncate leaves with a narrower border of elongate cells.